PENDAMPINGAN PEMASARAN UMKM PEMPEK DI PASAR KULINER 26 ILIR KOTA PALEMBANG PADA MASA PANDEMI COVID 19 - Anugrah Utama; Hatidah Hatidah; Ujang Ujang (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
The pandemic era with various restrictions on people's movement continued throughout 2021, causing the economy in various sectors and regions in Indonesia to be affected, including the Micro, Small and Medium Enterprises (UMKM) sector in the Palembang area, South Sumatra which was severely affected. The problem is that many MSMEs are out of business due to management and marketing strategies and are not well known by consumers, as well as a lack of understanding of the importance of digital marketing. One of the impacts of the pandemic is in the culinary world, namely the sale of the typical food of the city of Palembang, Pempek. Many Pempek MSME entrepreneurs feel the direct impact of the Covid 19 attack on the sales of Pempek. The decline in sales turnover of pempek as a typical souvenir from the city of Palembang has forced several pempek stalls in culinary tourism at Pasar 26 Palembang to close their shops. Through the Community Partnership Program (PKM) to overcome these problems, the team proposed priority issues that were agreed upon and resolved. The purpose of this activity is to foster MSMEs, help overcome the problems faced by MSMEs in running their business and increase people's income. The results of this activity: 1) Availability of raw material stock of ground fish 2) Availability of freezer and vacuum sealer machines 3) Achievement of marketing and promotion on social media Pempek out of South Sumatra.